The effect of murottal Al Qur'an on the dysmenorrhea intensity among senior high school students - Az Zahra, Fathimah; Wahyuliati, Tri (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Dysmenorrhea or pain during menstruation is due to excessive contractions during the sloughing of the uterine wall with symptoms of cramping pain in the lower abdomen. The incidence of primary dysmenorrhea in Indonesia is 54.89%. However, many teenagers do not know how to manage the pain. The pharmacological therapy of dysmenorrhea includes painkillers and anti-prostaglandin, while the non-pharmacological approach includes distraction therapy. One of the distraction therapy that is easy to do is murottal Al-Qur’an. Objective: This study observed the role of listening to murottal Al-Qur’an on the intensity of dysmenorrhea among senior high school students. Methods: The design of this study is a quasi-experimental pretest-posttest with a control group design. There were 100 subjects aged 15-18 years old. The sampling technique applied purposive sampling. Data analysis of this study applied Wilcoxon, Mann-Whitney, relative risk (RR), and number needed to treat (NNT) test. Results: The mean pain level in the experimental and control group were 5.42 and 5.56 before intervention. After therapy, the pain level decreased to 2.86 and 5.30 in the experimental and control group, respectively. There was a significant difference in the pain level before and after in the experiment group (p <0.001). Relative risk showed that murottal intervention decreases the pain level by 3.267 times. NNT of the study was 1.467. Conclusion: Murottal Al-Qur’an significantly reduced the degree of pain with a p-value <0.001